Support for Principals in Compulsory Schools in Iceland – What They Get and What They Wish For - Róbertsdóttir, Sigurbjörg; Björnsdóttir, Amalía; Hansen, Börkur (Menntavísindasvið Háskóla Íslands, 2020)
The conditions in which principals work have changed drastically over the past decades. Many aspects of the principal’s role have become more complex, and the demands of the job continue to escalate. These changes, in addition to causing a heavier workload, have increased the need for support for both new and experienced principals. The main purpose of this research project was to study the support that compulsory school principals in Iceland received when they first started their careers, the kind of support they now receive, and their perceived needs for support on the job. Furthermore, principals were asked from what source most of the support should come.Constructive support is vital to principals, both in the early stages as well as later in their career. Boerema (2011) asserts that constructive support for school principals should be provided both in the beginning and throughout their career. He states that it is becoming more common for principals to quit their jobs or change careers after a few years. Evans (2010), Hargreaves and Fink (2006), and Meyer, Macmillan and Northfield (2011) share this observation and point out that frequent changes of principals can have negative effects on school staff, stability in school operations, and student achievement. In the same way, Honig (2012) states that constructive support of school principals can facilitate better leadership practices and improve schooling.Support to school principals can be provided in various ways. Preparation and support are quite strategic in some countries, while not in others (Pont, Nusche og Moorman, 2008). According to Lee (2015), the support can range from assisting new principals with practical matters concerning the management and operation of schools to personal support and development on the job. Whitmore (2017) outlines several forms of coaching as types of support, ranging from formal to informal. According to Retelle (2010), mentoring and coaching are support schemes of a similar nature that emphasise context-based learning. In ...